Local structure change evidenced by temperature-dependent elastic measurements: Case study on Bi1/2Na1/2TiO3-based lead-free relaxor piezoceramics - Dittmer, Robert; Jo, Wook; Webber, Kyle Grant; Jones, Jacob L.; Rödel, Jürgen (Journal of Applied Physics, 2014)
The temperature-dependent Young's modulus Y(T) of the lead-free piezoceramics of 0.8Bi(1/2)Na(1/2)TiO(3)-0.2Bi(1/2)K(1/2)TiO(3) (20BKT) and 0.96(0.8Bi(1/2)Na(1/2)TiO(3)-0.2Bi(1/2)K(1/2)TiO(3))-0.04 BiZn1/2Ti1/2O3 (4BZT) is measured with the impulse excitation technique and contrasted with corresponding dielectric and structural data. While the dielectric properties suggest a phase transition, the high resolution XRD patterns remain virtually unchanged from room temperature up to high temperatures, confirming no change in their long-range order. In contrast, the elastic properties indicate a broad and diffuse ferroelastic transition denoted by a minimum in Y(T). By analogy to the elastic and dielectric data of PbZrxTi1-xO3 and PLZT, it is concluded that 20BKT and 4BZT are relaxors with polar nanoregions embedded in a metrically cubic matrix. Interestingly, no indication for the freezing temperature was reflected in any of the employed measurement techniques. From the saturation of Y(T), it is suggested that the Burns temperature may be approximated as 700 degrees C. Moreover, it is found that the modification with the ternary end-member BiZn1/2Ti1/2O3 results in an increase in Young's modulus. A comparison with the Bi1/2Na1/2TiO3-BaTiO3-K0.5Na0.5NbO3 yields the same results. (C) 2014 AIP Publishing LLC.